Pengaruh Transaksi Perbankan Berbasis Elektronik Terhadap Kinerja Perbankan - Henni P. Manalu P. Manalu; Tri Joko Prasetyo Prasetyo; Liza Alvia Alvia (Ridwan Institute, 2022)
In this situation, the banking sector is experiencing an impact that must be worried about, so that many policy efforts are carried out to overcome it in this epidemic situation. During the Covid-19 pandemic and also in the all-electronic era like today, the necessity for digital transformation in any industry is an important event that can never be ignored. The purpose of this study is expected to be able to complete empirical evidence on the effect of electronic-based banking transactions on fee-based income and profitability. This study uses a secondary data type method, namely research data obtained by researchers indirectly through intermediary media which are generally in the form of recorded evidence or historical reports that have been compiled published by banking companies. The effect of electronic-based banking transactions as proxied by the number of ATM, mobile banking and internet banking transactions on banking performance as proxied by fee-based income and Return on assets in conventional general banking registered with the Financial Services Authority in 2019-2020.